Identifying seminal papers in the Australasian Journal on Ageing 1982–2011: A Delphi consensus approach. (28th October 2013) - Parkinson, Lynne; Richardson, Kristy; Sims, Jane; Wells, Yvonne; Naganathan, Vasi; Brooke, Elizabeth; Lindley, Richard
Abstract : Aims: The aim of this study was to identify seminal Australasian Journal on Ageing papers published over 30 years through a Delphi consensus process. Method: The main data collection was a three‐round Delphi consensus study with 38 past and current members of the Australasian Journal on Ageing Editorial Board, Editorial Team and Management Committee. Results: Three papers were agreed as top‐ranking. One of the top‐ranking articles was also highly cited. One article was published in the 1990s, two in 2001. Conclusions: While it is difficult to judge how well the top‐ranking papers represent seminal papers arising over 30 years, these papers do represent three different research strengths in Australasia, they do span three different disciplines, and they do reflect some of the diversity that characterises ageing research in Australasia over 30 years.